A descriptive, cross-sectional study characterizing bone erosions in rheumatoid arthritis and gout by ultrasound. Issue 9 (September 2016) - Ventura-Ríos, Lucio; Hernández-Díaz, Cristina; Sanchez-Bringas, Guadalupe; Madrigal-Santillán, Eduardo; Morales-González, José; Pineda, Carlos
Abstract The aim of this study is to characterize bone erosions in metatarsal heads (MTH) in rheumatoid arthritis (RA) and gout by grayscale ultrasound. In a descriptive, cross-sectional study, we evaluated 40 patients with RA and 40 with gout, both diagnosed according to the American College of Rheumatology/European League Against Rheumatism criteria, respectively. All patients had bone erosion demonstrated by ultrasound, which was used, following OMERACT criteria, to describe the shape, size, number, border definition, overhanging margin, topography (intra- or extra-articular), and distribution (over dorsal, medial, lateral, or plantar aspect) of the lesions in the MTH. Descriptive statistics were used and a concordance exercise between two ultrasonographers blinded to the diagnosis was performed. Bone erosions in RA were observed most frequently at the plantar and lateral aspect of the fifth MTH, round in 96 %, small-sized (2.43 ± 0.9 mm), intra-articular (100 %), and single (75 %). Few bone erosions had a well-defined border an overhanging margin while in gout were found most frequently in the medial and dorsal aspect of the first MTH, single in 71 %, intra-articular in 100 %, and of median size (4.0 ± 2.3). For shape, 51 % was round and 49 % was oval. A well-defined border was present in 39 %, and an overhanging margin in 62 %. Inter-rater reliability kappa was excellent (0.81, 95 % CI 0.56–1.00). Some characteristics of bone erosions in RA, including shape, size, ill-defined border, and localization in the fifth MTH could distinguish the lesions from gout. Grayscale US has excellent reliability to describe bone erosions in RA and gout.